Thai garment industry organisational characteristics and strategic factors that affect corporate performance - Nimlaor, Chavalit; Trimetsoontorn, Jirasek; Fongsuwan, Wanno (My University, 2015)
This study concerns the modelling and analysis of the Thai Garment Manufacturers Association's members using both quantitative and qualitative research methods. With the garment industry expected to continue its contraction and loss of exports due to increased global competitiveness, the researchers wish to use decades of industry knowledge to conduct further analysis. Quantitative data was obtained from 178 entrepreneurial members while qualitative data was gathered from in-depth interviews of ten senior executives using simple random sampling (purposive sampling) while using partial least square (PLS-graph) software to apply structural equation modelling analysis. Results showed the hypotheses had a significance level of p ≤ 0.05, having a significant influence on corporate strategy and organisational characteristic. Findings concluded that industry entrepreneurs must have clear strategic leadership visions keeping pace with rapidly developing sector changes. Finally, industry leaders must also respond immediately to their customers while maintaining their margins and a competitive advantage.
Keywords: Apparel; Corporate performance; Corporate strategy; Enterprise development; Garment industry; International management; R&D